Co-Enzyme Q10 and n-3 Polyunsaturated Fatty Acid Supplementation Reverse Intermittent Hypoxia-Induced Growth Restriction and Improved Antioxidant Profiles in Neonatal Rats - Kay D. Beharry; Charles L. Cai; Michael M. Henry; Sara Chowdhury; Gloria B. Valencia; Jacob V. Aranda (MDPI AG, 2017)
Neonatal intermittent hypoxia (IH) increases the risk for many morbidities in extremely low birth weight/gestational age (ELBW/ELGA) neonates with compromised antioxidant systems and poor growth. We hypothesized that supplementation with coenzyme Q10 (CoQ10, ubiquinol) or n-3 polyunsaturated fatty acids (PUFAs) during neonatal IH improves antioxidant profiles and somatic growth in neonatal rats. Newborn rats were exposed to two IH paradigms at birth (P0): (1) 50% O2 with brief hypoxic episodes (12% O2); or (2) room air (RA) with brief hypoxia, until P14 during which they received daily oral CoQ10 in olive oil, n-3 PUFAs in fish oil, or olive oil only from P0 to P14. Pups were studied at P14 or placed in RA until P21 for recovery from IH (IHR). Body weight and length; organ weights; and serum antioxidants and growth factors were determined at P14 and P21. Neonatal IH resulted in sustained reductions in somatic growth, an effect that was reversed with n-3 PUFAs. Improved growth was associated with higher serum growth factors. CoQ10 decreased superoxide dismutase (SOD) and glutathione, but increased catalase, suggesting reduced oxidative stress. Further studies are needed to determine the synergistic effects of CoQ10 and n-3 PUFA co-administration for the prevention of IH-induced oxidative stress and postnatal growth deficits.